A Priority-Based Public Communication Strategy Model for Land Acquisition in Public Interest Development: An AHP Approach - Harison Mocodompis; Sumardjo; Popong Nurhayati; Andi Tenrisau (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Compulsory land acquisition for public infrastructure frequently generates social conflict and weakens institutional legitimacy. Despite the importance of communication in managing multi-stakeholder relationships, no empirically validated, priority-weighted communication model exists for land acquisition governance. This study develops and validates a stakeholder-centered communication model using the analytic hierarchy process within a mixed-methods approach combining analytic hierarchy process, focus group discussions, and expert interviews. Data were collected from 164 multi-stakeholder respondents across five Indonesian provinces to identify communication priorities for effective land acquisition governance. The results were further validated through focus group discussions and expert consultations. The AHP analysis demonstrated a high level of consistency (CR = 0.000862) and identified Stakeholder Engagement as the most critical communication factor (weight = 0.527), indicating that communication failures stem primarily from relational rather than informational deficiencies. Local government emerged as the most influential communication actor (0.265), surpassing national regulatory authorities (0.103). Open and inclusive interaction was identified as the principal communication objective (0.317), while the communication bridge strategy emphasizing two-way dialogue, aspiration integration, and information quality control ranked as the highest-priority intervention (0.326). The proposed SCC Model offers an evidence-based and replicable framework for strengthening communication, stakeholder coordination, and governance effectiveness in land acquisition programs.